Housing and Tax Policy. Issue 2 (March 2016) - ALPANDA, SAMI; ZUBAIRY, SARAH
Abstract : This paper investigates the effects of housing‐related tax policy measures on macroeconomic aggregates using a dynamic general‐equilibrium model featuring borrowing and lending across heterogeneous households, financial frictions in the form of collateral constraints tied to house prices, and a rental housing market alongside owner‐occupied housing. We analyze the effects of various tax policies and find that they all lead to significant output losses, with large long‐run tax multipliers of around 2. Among them, reducing the mortgage interest deduction is the most effective in raising tax revenue per unit of output lost, whereas reducing the depreciation allowance for rental income is the least effective.